Antioxidant Retention and Physicochemical Characterization of Instant Ginger Powder Formulation as a Functional Beverage - Pijaryani, Indria; Muh. Taufiqurrahman (Asian Journal of Healthcare Analytics, 2026)
This study aims to formulate an instant ginger rhizome extract powder and comprehensively evaluate its physicochemical characteristics and antioxidant retention capacity as a functional beverage. This experimental research employed four variations of ginger powder concentration (0%, 5%, 10%, and 15%) using the wet granulation method. Evaluation results indicated that all formulations met the required standards, with moisture content below 5% and favorable flowability. The 15% formulation (F3) proved to be the most optimal, demonstrating strong antioxidant activity with an IC50 value of 65.50 ppm. Overall, this formulation produces a powdered beverage with excellent physicochemical stability and measurable nutraceutical efficacy, making it a viable candidate for functional food.